Engineering Pseudomonas putida for production of 3-hydroxyacids using hybrid type I polyketide synthases - Matthias Schmidt; Aaron A. Vilchez; Namil Lee; Leah S. Keiser; Allison N. Pearson; Mitchell G. Thompson; Yolanda Zhu; Robert W. Haushalter; Adam M. Deutschbauer; Satoshi Yuzawa; Lars M. Blank; Jay D. Keasling (Metabolic Engineering Communications)
Engineered type I polyketide synthases (T1PKSs) are a potentially transformative platform for the biosynthesis of small molecules. Due to their modular nature, T1PKSs can be rationally designed to produce a wide range of bulk or specialty chemicals. While heterologous PKS expression is best studied in microbes of the genus Streptomyces, recent studies have focused on the exploration of non-native PKS hosts. The biotechnological production of chemicals in fast growing and industrial relevant hosts has numerous economic and logistic advantages. With its native ability to utilize alternative feedstocks, Pseudomonas putida has emerged as a promising workhorse for the sustainable production of small molecules. Here, we outline the assessment of P. putida as a host for the expression of engineered T1PKSs and production of 3-hydroxyacids. After establishing the functional expression of an engineered T1PKS, we successfully expanded and increased the pool of available acyl-CoAs needed for the synthesis of polyketides using transposon sequencing and protein degradation tagging. This work demonstrates the potential of T1PKSs in P. putida as a production platform for the sustainable biosynthesis of unnatural polyketides.